Knowledge of Technology Poultry Production and Entrepreneurship For Development of Indigenous Chicken Farms in Indonesia - Palmarudi Mappigau; Muhammad Yunus Amar (Journal of Business and Management Review, 2020)
The objective of this study is to analyze the knowledge of technology poultry production and entrepreneurship for the development of indigenous chicken farms. The research location Sidrap and Bone regencies, South Sulawesi Province, Indonesia. The data collected through direct observation and structured interviews with 96 indigenous chicken farmers. The data analyzed by descriptive statistics and Spearman's Rank correlation. The results showed that the development of indigenous chicken farms was decreasing and not increasing in the number of chickens, the knowledge of farmer respondents in technology poultry production and entrepreneurship was categorized as inadequate. The results show that in the technology poultry production, knowledge of suitable feed, and control and prevention of disease have a positive and significant relationship with the development of indigenous chicken farms. In entrepreneurial knowledge, knowledge of results-oriented and opportunity-seeking have a positive and significant relationship with the development of indigenous chicken farms. The conclusion, the technology poultry production, and entrepreneurship knowledge have an important role in the development of indigenous chicken farms